2015
DOI: 10.1016/j.laa.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Local Lie derivations of nest algebras

Abstract: Let N be a nest on a Hilbert space H and Alg N be the associated nest algebra. We prove that every local Lie derivation from Alg N into B(H) is a Lie derivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…It is known that every element in M can be written in the form λI+ n i=1 [A i , B i ], where λ ∈ C and A i , B i ∈ M(see, [7]). If the unit I can not be written in the form The following result is proved in [8]. We show it by Theorem 3.1 as an alternative method.…”
Section: Local and 2-local Lie Derivationsmentioning
confidence: 88%
See 1 more Smart Citation
“…It is known that every element in M can be written in the form λI+ n i=1 [A i , B i ], where λ ∈ C and A i , B i ∈ M(see, [7]). If the unit I can not be written in the form The following result is proved in [8]. We show it by Theorem 3.1 as an alternative method.…”
Section: Local and 2-local Lie Derivationsmentioning
confidence: 88%
“…Also in this paper [9], the authors characterize 2-local Lie derivations on B(X). Later, L. Chen, and F. Lu [8] prove that every local Lie derivation from a nest algebra algN into B(H) is a Lie derivation, where N is a nest on the Hilbert space H. Quite recently, L. Liu [21] characterizes 2-local Lie derivations on a semi-finite factor von Neumann algebra with dimension greater than 4.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that each local Lie derivation from B(X ) into itself is a Lie derivation. Later, Chen and Lu [3] proved that each local Lie derivation of nest algebras on Hilbert spaces is a Lie derivation. In [14,15], Liu and Zhang proved that the same is true for local Lie derivations on von Neumann algebras and a certain class of triangular algebras, respectively.…”
Section: More Generally a Linear Map δ Of U Is Called A Lie Derivation If δ([A B]) = [δ(A) B] + [A δ(B)]mentioning
confidence: 99%
“…Moreover, it was proved in [7,Corollary 6.4] that every Lie n-derivation on T (N ) is standard. Chen and Lu [11] showed that every local Lie derivation (n = 2) from T (N ) into B(H) is a Lie derivation. In fact, each local derivation on the nest algebra is an inner derivation [14,Theorem 2.6].…”
Section: B-module Let T =mentioning
confidence: 99%
“…Then the following question seems natural: When is the local Lie n-derivation as Lie n-derivation? If n = 2, it was studied in [11,25,26,27] on the nest algebras, generalized matrix algebras, von Neumann algebras, triangular algebras, respectively. To the best of our knowledge, there is not any article treating the situation of n ≥ 3.…”
Section: Introductionmentioning
confidence: 99%